Klasifikasi Keunggulan Shuhuf Sahabat Masa Pra-Usmani: Implementasi dan literasi - Rifai, Mirwan Sudarmawan; Miswar, Andi; S, Sohrah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research will provide a deeper treasury of Islam particularly on the history of the codification of the Qur’an. The focus of the discussion of this research is on the primacy of the shahuf of some companions in the Pre-Ottoman period. Practically this research will justify the perseverance of the Companions in the field of literacy as the implementation of the first commandment of the Qur’an both with the help of memorization and closeness to the Prophet. Additionally, this study will also discuss the strategic role of the Companions in the collection of the shahuf of the Qur’an during that period. This would encourage a sustained discussion of Qur’anic codification in the pre- and post-Ottoman periods. This research is expected to reference and enrich the scholarly literature as well as make a contribution to the religious dialogue, and strengthen the understanding of discourse and discursive complexity in the Qur’anic codification process.